A peptide-AIEgen nanocomposite mediated whole cancer immunity cycle-cascade amplification for improved immunotherapy of tumor. (June 2022) - Dai, Jun; Dong, Xiaoqi; Liu, Rui; Chen, Biao; Dong, Xiyuan; Wang, Quan; Hu, Jing-Jing; Xia, Fan; Lou, Xiaoding
Abstract: Immunotherapy maintains the cancer-immunity cycle via re-activating the immune system, so as to achieve the purpose of anti-tumor. However, the response rate of current tumor immunotherapy strategies is still low. Even the most reported immune checkpoint block (ICB), the objective response rate (ORR) is only about 10–30%. Here, aiming at obtaining a higher response rate, we designed a cascade amplification nanocomposite consisting of the immune adjuvant polyinosinic:polycytidylic acid [Poly (I:C)] and aggregation-induced emission luminogen (AIEgen)-modified modular peptide (named PMRA). The PMRA includes: D PPA-1 peptide (P), an immune checkpoint inhibitor; PLGLAG peptide (M), a matrix metalloproteinase 2 (MMP-2) responsive sequence to promote the release of D PPA-1; RRRRRRRR peptide (R), for loading the Poly (I:C); PyTPA (A), a photosensitizer with AIE property. In cancer-immunity cycle, photodynamic therapy (PDT) mediated by PyTPA promotes the release of tumor-associated antigens (TAAs), and primes T lymphocytes. The cytokines coming from the stimulation of PDT and Poly (I:C) promote the activation of T lymphocytes. The high level of chemokines in tumor microenvironment promotes immune cells migration and infiltration in tumor with the assistance of PDT. Finally, through ICB with D PPA-1 peptide, T lymphocytes enhance the recognition of tumor cells and killing tumor cells. Immunogenic cell death induces the release of more TAAs, which will enter the next cycle and complete the full-loop again. Taking advantages of whole cancer-immunity cycle, the cascade amplification nanocomposite achieved almost 100% ORR in vivo . This concept of whole cancer-immunity cycle enhanced immunotherapy provides a novel perspective for tumor treatment.